Encounters and evades between art and photography - Latorre, Jorge (2022)
Through a rundown of the history of photography in relation to the arts, and an analysis of the historiographical milestones of photographic art, this article proposes some important questions about the differences between photography and paintings, which makes it especially suitable for the artistic expression of our time. The underlining proposal is that the debate about photography as art -or what time of photography is artistic and whatother kind is not is not- is not important, but instead it has to be considered the analysis of photography in the occidental artistic panorama, and the enormous consequences that it has had and continues to have on the reflection about creativity and the reality of our time.